Combined Nasal, Oropharyngeal Povidone Iodine Plus Glycyrrhizic Acid Sprays, Accelerate Clinical and Laboratory Recovery and Reduces Household Transmission of SARS-CoV-2: A Randomized Placebo-Controlled Clinical Trial - Elsersy, Hazem E.; Zahran, Magdy A. H.; Elbakry, Abd-Elazeem; Abd-Elwahab, Mohamed; Ahmed, Mohamed Milegy; Elgandy, Mohamed Salah; Mohammed, Eman H. M.; Elewa, Nourhan M. (Frontiers in Medicine, 2022)
The COVID-19 pandemic is still posing challenging health and economic problems. Effective broad-spectrum antiviral therapy is urgently needed for the control of early SARS-CoV-2 infection to limit its spread and mutations. In this randomized placebo-controlled clinical study, we tested the effects of intranasal and oropharyngeal delivery of a compound of povidone-iodine 0.5% and glycyrrhizic acid 2.5 mg/ml on the laboratory (PCR) and clinical recovery from SARS-CoV-2 patients and their household contacts. 353 patients suspected of having COVID-19 infection were screened by chest CT and nasopharyngeal swab tests (PCR). 200 patients were randomly allocated to two equal groups: treatment and placebo groups. Treatment accelerated the recovery of PCR on days 4, 7, and 10, as evidenced by PCR-positive patients (70, vs. 99%, 20 vs. 65%, 1 vs. 10%) in both the treated and placebo groups, respectively. Treatment enhanced the early recovery of symptoms [day 7.6 ± 2 (CI 7:8.3) vs. 8.9 ± 2 (CI 8.3:9.6)]. Treatment promoted early recovery of anosmia and ageusia [5.6 ± 1 (CI, 4.8:6.4) vs. 11 ± 3 days, (CI, 10.8:12)] in both the treated and control groups (P < 0.0001). There was a notable reduction in transmission of the virus among the household close contacts in the treatment group (4%) vs. 76% in the placebo group. Combined PVI-GA nasal and oropharyngeal spray accelerates both laboratory and clinical recovery of SARS-CoV-2 infected patients in the early phases of the disease and reduces the household spread of the virus; thus, it may play an important role in controlling coronavirus outbreaks. Clinical Trial Registration https://pactr.samrc.ac.za, PACTR202101875903773.